(untitled) (Contemporary Mathematics, 2023)
In this note, we discuss a common fixed point for a family of self-mapping defined on a metric-type space and satisfying a weakly contractive condition. In our development, we make use of the λ-sequence approach and of a certain class of real-valued maps. We derive some implications for self-mappings on quasi-pseudometric type spaces.